Analysis and Design Information System of Recapitulation Jam Minus P5M - Eko Abdul Goffar; Radix Rascalia; Rida Indah Fariani (Institut Teknologi Dirgantara Adisutjipto, 2019)
Pertemuan 5 Menit (P5M) is a routine activity that is always carried out by instructor in Politeknik Manufaktur Astra (Polman Astra) to students in each Unit Pelaksana Teknis (UPT) before or after lectures begin. Students who do not follow or violate the rules at the time of P5M will get a penalty in the form of minus hours. Minus hours are penalties given to students. Data minus hours of P5M are recorded using a form that is recapitulated one by one for every week and inputted into academic information system Polman Astra. The input time for minus P5M clock data is 565 minutes. Therefore we need an information system that can help overcome or automate it. In this research an analysis and design will be carried out using the System Development Life Cycle (SDLC) stages with extreme programming methodology which will reduce the recapitulation time from 565 to 280 minutes.